2013
DOI: 10.1364/ao.52.002346
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet packet energy characterization of low velocity impacts and load localization by optical fiber Bragg grating sensor technique

Abstract: The low velocity impacts (LVIs) monitoring based on optical fiber Bragg grating (FBG) sensors have attracted more attention in recent years. The center wavelength migrations of FBG sensors were determined by strain and residual strain during and after LVI on composite material structure. We presented a method to discriminate the energy characters of LVI response signals related to LVI locations. By analyzing the wavelet packet energy spectra of LVI response signals monitored by FBG sensors, the sixth node's en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In practical applications, R is estimated by a finite number of data vectors : 1 (12) where R is the estimation of R , and L is the number of the snapshots. Hence, the output power can be expressed as…”
Section: Mvdr Beamforming Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In practical applications, R is estimated by a finite number of data vectors : 1 (12) where R is the estimation of R , and L is the number of the snapshots. Hence, the output power can be expressed as…”
Section: Mvdr Beamforming Algorithmmentioning
confidence: 99%
“…Riberiro et al [10] and Jang et al [11] used FBG sensors and the neural network method to obtain the location of impact source on the composite structure, respectively. Lu et al [12] proposed support vector regression to determine impact source on the composite structure by using FBGs. Jiang et al [13] used the extreme learning machine and FBG sensor network to obtain the location of impact.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, fiber Bragg grating (FBG) [4], [5] is shown as promising sensors in area localization for its advantages of anti-electromagnetic interference, easy to establish sensing network and install without destroying the structures. Lu et al [6] studied the low velocity impact localization of the composites, and showed that FBG sensor technology can be used to detect the impact signal and realize the impact localization. When the impact signal is detected, the next key factor of the low velocity impact area localization is the area localization algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency variation signal generates specific strain fields along FBG axis, which leads to changes of fiber grating period and refractive index. The characteristics can be used to make the position and identification of acoustic emission source so that serious damages are avoided [6][7][8].…”
Section: Introductionmentioning
confidence: 99%